2020
DOI: 10.52764/jms.20.28.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Thrombocytopenia in Patient With Malaria Presented to Khyber Teaching Hospital Peshawar, Pakistan

Abstract: Background: Malaria is a fatal infectious disease which  is associated with numerous complications and has a profound effects on the blood indices. Thrombocytopenia is frequently reported among the patients with malaria though it is not an indication of the severity of the disease.   Objective: The aim of the current study is to observe the hematological changes particularly the incidence of thrombocytopenia among the patients with malaria presented to the Khyber Teaching Hospital, Peshawar.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
4
6
0
1
Order By: Relevance
“…Amongst patients with thrombocytopenia, grade 1 thrombocytopenia was observed in 50% patients, grade 2 in 25.33% patients, grade 3 in 15.33% patients while grade 4 thrombocytopenia was observed in 9.33% patients. In accordance with our study, another study reported almost similar results 19 . The precise cause of malarial thrombocytopenia is uncertain.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Amongst patients with thrombocytopenia, grade 1 thrombocytopenia was observed in 50% patients, grade 2 in 25.33% patients, grade 3 in 15.33% patients while grade 4 thrombocytopenia was observed in 9.33% patients. In accordance with our study, another study reported almost similar results 19 . The precise cause of malarial thrombocytopenia is uncertain.…”
Section: Discussionsupporting
confidence: 93%
“…An earlier study done by MUHAMMAD ASIF et al reported that p.vivax malaria is more common in Pakistan as compared to p. falciparum 18 . Another study carried out by Hamza Ali Khan et al observed similar results and reported that p.vivax malaria was present amongst 92.7% patients while p. falciparum was observed only in 7.3% patients 19 . In the current study, the overall frequency of thrombocytopenia amongst 150 patients with malaria was 90% (n=135).…”
Section: Discussionsupporting
confidence: 52%
“…One or more attacks of acute tonsillitis per year is common in children of primary school age. 7 Tonsils undergo involution at puberty, but this can be hampered if the tonsillar tissues and cells are not permanently damaged. Children who experience acute tonsillitis with adequate treatment are at lower risk of experiencing enlarged tonsils compared to patients who experience recurrent tonsillitis or chronic tonsillitis.…”
Section: Resultsmentioning
confidence: 99%
“…Tarasov and Morozov also conducted health checks on children and adults, found a total of 190-230 ENT diseases per 1,000 population, and 38.4% of them suffered from chronic tonsillitis. 7,8 World Health Organization In 2013, the number of cases of chronic tonsillitis was estimated at 287,000 children under 15 years. 9 Research conducted at Sarawak Hospital in Malaysia in the period July 2003 to June 2004, out of 657 patients with chronic tonsillitis, 342 men (52%) were found and 315 women (48%).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus, Klebsiella pneumonia, Streptococcus spp., and Proteus spp. were the most prevalent vaginal microbes (18). However, BV are both vaginal dysbioses with fewer lactobacilli (19).…”
Section: Introductionmentioning
confidence: 99%